SENYAWA FITOKIMIA PADA COOKIES JENGKOL (Pitheocolobium jiringa) - Thomas Ghozali; Supli Efendi; Hendra Abdul Buchori (JURNAL AGROTEKNOLOGI, 2013)
The aims of the research were determine the proper comparison between jengkol flour and wheat flour in making cookies as a result of differences in temperature roasting, and determine the response to that produced both chemical and organoleptic as well as the existence of multiple phytochemical compounds. Research methods were conducted preliminary research and primary research. Early research was included analysis of jengkol, determined the best comparison of jengkol and wheat flour for cookies making. The experimental design used in this study randomized block design with three factorial design and three times replication. The variables were used roasting temperature (Y) with three level i.e Y1 (150°C), Y2 (160°C), and Y3 (170°C); the periode of roasting (X) with three levels i.e X1 (1:1), X2 (1:3), and X3 (1:5). Based on sensory evaluation showed that X3Y2 was preferred for 160°C roasting temperature with comparisons of jengkol flour and wheat flour 1:5. Phytochemical compounds in the cookies were detected phenolics, flavonoids, alkaloids, steroids, saponins, and tannins.Keywords: flour, jengkol, roasting temperature, phytochemical compounds